The Brazilian state in the light of Marxist tradition: the relevance of bourgeois autocracy today - Santos, Liliam dos Reis Souza (Argumentum, 2026)
This text highlights the particularities of the formation and current historical situation of the Brazilian State based on the theory and methodology of historical-dialectical materialism. Through theoretical and documentary research, it presents the characteristics of political power and the State in Brazil. It places them within the context of economic concentration and the country’s historical landmarks, with an emphasis on the contemporary context and the rural and rentier class fractions. It concludes that, in Brazil, an autocratic State predominates, even under the guise of democracy, which restricts and alienates society from economic and political participation.